The scourge of carbapenem resistant Enterobacteriaceae: how to fight back - Samel, Samveda S.; Mandrekar, Suruchi S.; Walse, Prashant N.; Iqubal, Syed Haroon; Bafna, Raja Y.; Singh, Mrityunjay K.; Alwani, Paresh P.; Dholu, Bharatkumar D. (International Journal of Advances in Medicine, 2024)
The Enterobacteriaceae species cause both community acquired and health care associated infections like bloodstream infections, ventilator-associated pneumonia, intra-abdominal infections and urinary tract infections. Carbapenem-resistant Enterobacteriaceae (CRE) have been included in the list of global priority pathogens (GPP) declared by WHO in 2017. These infections pose a serious threat due to the associated significant morbidity and mortality. The mechanisms of antimicrobial resistance in these organisms are numerous; however, β-lactamase genes carried on mobile genetic elements are a key mechanism for the rapid spread of these antibiotic-resistant strains on a global scale. The carbapenem resistance (CR) in Enterobacteriaceae has been recognized for the past two decades, but the carbapenemase-producing Enterobacteriaceae (CPE) has been a more recent issue and is spreading at an alarming pace worldwide. In this article, we conducted a systematic literature search of the PubMed, Embase, Web of Science and Cochrane Library databases to identify relevant studies that reported the epidemiology and the outcomes for hospitalised patients with confirmed infections due to CRE and carbapenem-susceptible Enterobacteriaceae (CSE) published between 1 January 2010 and 30 August 2023.The results emphasize that patients with CRE infection still face a greater risk of mortality and need an urgent need for newer antibiotics and appropriate treatment regimens to reduce the risk of morbidity and mortality.